MODEL LATIHAN SERVIS FOREHAND TENIS MEJA UNTUK ATLET PEMULA USIA 12 TAHUN KE BAWAH - Risang Bhirawan; Sri Purnami; Mulyani Surendra (Fakultas Ilmu Keolahragaan UM, 2015)
Abstract: Forehand service often becomes a beginner athlete weakness in Table Tennis Association Tri Dharma Malang. This research aims to solve the existing problems by developing forehand service exercise models for beginner athletes. The method which researchers used refers to the development model of Borg and Gall. Data analysis technique which is being used is the qualitative and quantitative analysis in the form of a percentage. The trial results of small groups based on all product specifications is 84.0 to 84.3% and testing a large group is 86.8 to 87.4%. So that the exercise model of forehand service to the beginner athlete of Tri Dharma Malang PTM can be used.Key words: model of training, forehand service, table tennis.Abstrak: Servis forehand cenderung menjadi kelemahan atlet pemula PTM Tri Dharma Malang. Penelitian ini bertujuan membuat model latihan servis forehand tenis meja di PTM Tri Dharma. Peneliti menggunakan prosedur pengembangan (research and development) dari Borg and Gall.Teknik analisis data yang digunakan adalah analisis kuantitatif dan kualitatif berupa persentase.Hasil uji coba kelompok kecil adalah 84,0 - 84,3% dan uji coba kelompok besar 86,8-87,4%. Sehingga model latihan servis forehand pada atlet pemula dapat digunakan di PTM Tri Dharma Malang.Kata kunci: model latihan, servis forehand, tenis meja.